Implementation of Mental Health Policies toward Indonesia Free Restraint - Dumilah Ayuningtyas; Marisa Rayhani; Misnaniarti Misnaniarti; Asri Nur Maulidya (Policy & Governance Review, 2018)
Mental health disorders are still one of the most prominent health problems in the world, including in Indonesia. There is still a misguided stigma and discrimination on people with mental disorders, so more than 56,000 of them experience restraint. This study aims to determine the eﬀorts and review the implementation of Law no. 18/2014 about Mental Health until 2017. This is a policy study using literature review. Descriptive exploration is done using a policy analysis framework in the implementation phase based on Edwards III model. The unit of analysis is mental health policy in Indonesia. The results show that only a few local governments initiate special mental health regulations as well as more operational programs. Activities are still focused on curative and rehabilitative eﬀorts. There has been prevention of deprivation through the ‘Indonesia Free Restraint’ program since 1977 but this has not gone well. The communication process encountered problems of unclear and inconsistent information. Moreover, not all local governments use the authority to regulate the mental health policy to mobilize resources. Law no. 18/2014 has not been implemented optimally. Not all implementers and policy targets are dedicated to direction of the Law. Neither not all aspects of mental health eﬀorts have programs, Standard Operating Procedure and coordination governance. Conversely, optimal implementation can be done by introducing it as an element of primary health in basic health service.